Retrospective evaluation of hypertrophic cardiomyopathy in 68 dogs. (24th March 2022) - Schober, Karsten E.; Fox, Phillip R.; Abbott, Jonathan; Côté, Etienne; Luis‐Fuentes, Virginia; Matos, Jose Novo; Stern, Joshua A.; Visser, Lance; Scollan, Katherine F.; Chetboul, Valerie; Schrope, Donald; Glaus, Tony; et al.
Abstract: Background: There is a lack of clinical data on hypertrophic cardiomyopathy (HCM) in dogs. Hypothesis/Objectives: To investigate signalment, clinical signs, diagnostic findings, and survival in dogs with HCM. Animals: Sixty‐eight client‐owned dogs. Methods: Retrospective multicenter study. Medical records were searched between 2003 and 2015. The diagnosis of left ventricular (LV) hypertrophy was made by echocardiographic examination. Results: Three hundred and forty‐five dogs with LV hypertrophy were identified, of which 277 were excluded. The remaining 68 dogs were 0.3 to 14 years old and predominantly <10 kg (85%), and without a sex predilection. Twenty‐four % were Shih Tzu and 24% terrier breeds. Most (80%) had a systolic heart murmur. Owner‐determined exercise intolerance (37%) and syncope (18%) were most commonly reported signs. The majority (84%) of dogs had symmetrical LV hypertrophy, whereas asymmetrical septal and LV free wall hypertrophy was observed in 9% and 6% of dogs, respectively. Isolated basal interventricular septal hypertrophy was not observed. Commonly recorded were systolic anterior motion of the mitral valve (60%) and LV diastolic dysfunction (89% of dogs where diastolic function was evaluated). Six dogs died unexpectedly, and 3 developed congestive heart failure. Known survival times were between 1 day and 114 months after diagnosis. Conclusions and Clinical Importance: Hypertrophic cardiomyopathy in dogs should be considered as a differential diagnosis if LV hypertrophy is identified. Small breed dogs are overrepresented, and it is uncommon for dogs with HCM to develop CHF although sudden death can occur.